68Ga-PSMA PET/CT Scan Leading to Diagnosis of PSMA-Positive Rectal Adenocarcinoma in a Patient With Prostate Cancer. (24th March 2022) - Norouzi, Ghazal; Rezaei, Alireza; Adinehpour, Zohreh; Amini, Hamidreza; Vali, Reza
Abstract: A 59-year-old prostate cancer patient, status post radical prostatectomy, was referred to our department for restaging with 68 Ga–prostate-specific membrane antigen (PSMA) PET/CT scan. Aside multiple metastatic lesions involving pelvic lymph nodes as well as the right femoral trochanter, a PSMA-positive rectal wall thickening was detected. Colonoscopy correlation and tissue diagnosis, recommended to rule out accompanying primary malignancy, confirmed the presence of rectal adenocarcinoma. This case signifies the importance of requesting pathological correlation for unexplained PSMA-positive lesions, emphasizing the potential role PSMA ligands may play in detecting occult second primary malignancies, especially synchronous/metachronous colorectal cancers.